1998
DOI: 10.1002/(sici)1096-8628(19980901)79:2<97::aid-ajmg4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis of idiopathic talipes equinovarus in a Texan population

Abstract: "Idiopathic" talipes equinovarus (ITEV) is a nonsyndromal congenital anomaly of one or both feet. Casting and surgery are often necessary to obtain correct foot alignment. In spite of treatment, residual deformities of the feet occur and calf muscles may be hypoplastic. The cause of ITEV is unknown but genetic factors have been postulated. Complex segregation analysis was performed on 173 ITEV families including 93 Caucasian and 48 Hispanic families. The recessive mixed model was the best fitting model and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 6 publications
3
29
0
1
Order By: Relevance
“…It is unknown if a single gene or multiple factors are involved. As previously noted, a number of investigators have proposed that idiopathic clubfoot has a genetic basis and is multifactorial in origin [2,5,7,8,26,34]. The association we found between increased internal hip rotation and idiopathic clubfoot suggests that the genetic basis of femoral and/or acetabular anteversion, which are the likely cause(s) for increased internal hip rotation, may play a role in the etiology of idiopathic clubfoot.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is unknown if a single gene or multiple factors are involved. As previously noted, a number of investigators have proposed that idiopathic clubfoot has a genetic basis and is multifactorial in origin [2,5,7,8,26,34]. The association we found between increased internal hip rotation and idiopathic clubfoot suggests that the genetic basis of femoral and/or acetabular anteversion, which are the likely cause(s) for increased internal hip rotation, may play a role in the etiology of idiopathic clubfoot.…”
Section: Discussionsupporting
confidence: 69%
“…Clubfoot, the most common congenital deformity of the musculoskeletal system, is believed to be etiologically multifactorial [2,5,7,8,10,14,26,34]. This means it is the result of the interaction of several genes and, to some extent, environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies using complex segregation analyses suggested a single incompletely dominant disease gene with unmeasured factors contributing to incomplete penetrance [56,71]. In a different study, segregation analysis suggested a recessive mixed model [16], and a complex segregation analysis in Pacific and Maori people demonstrated a single dominant gene with 33% penetrance [11]. A polygenic threshold model was also supported by the finding of the Carter effect, in which females require a greater genetic load in order to inherit the disorder than males [42].…”
Section: Etiologymentioning
confidence: 99%
“…In New Zealand Polynesian populations with a high incidence of talipes equinovarus, the best model of inheritance is autosomal dominant with a low penetrance (33%). 10 In other populations, regressive logistic models of complex segregation suggest a single major gene effect with autosomal recessive, 11 or autosomal dominant inheritance 12 and an additional effect (polygenetic or environmental factors) shared among siblings. 13 The genetic basis of talipes equinovarus is gradually being revealed.…”
Section: Introductionmentioning
confidence: 99%